Gene Expression in Aphelid Zoospores Reveals Their Transcriptional and Translational Activity and Alacrity for Invasion - Igor R. Pozdnyakov; Alexei O. Seliuk; Kristina O. Barzasekova; Sergey A. Karpov (Journal of Fungi)
In Aphelidium insulamus (Opisthokonta, Aphelida) zoospores, the expression of 7708 genes out of 7802 described genes was detected. For 589 of them, expression levels were shown to be more than 10 times higher than the median level. Among the highly expressed genes with known functions, the largest functional categories were “Cellular Metabolism”, “Protein Synthesis”, “Cell State Control”, and “Nucleic Acid Processing”. Unlike fungal zoospores, translational and transcriptional activity was demonstrated for A. insulamus zoospores. With increasing temperature, the expression of many zoospore genes changed dramatically; the expression of heat shock and chaperone protein genes multiplied more than 30 times, indicating the high sensitivity of aphelid zoospores and their response to environmental changes.